Misappropriation of Translation and Interpretation of Verses Related to the Divine Attributes in the Quran - Abdul Razak, Azizul Azra; Abdul Jalil, Hafizah; Mohammed Zabidi, Fakhrurrazi; Abdul Rahim, Mohd Hisyam (Journal of Social Transformation and Regional Development, 2021)
The deviation from the interpretation and translation of the meaning of the verses of the Qur’an in relation to the divine attributes occurs due to the inaccuracy of placement of meaning and translation. Such misinterpretation causes the god i.e. Allah s.w.t to look like a creature but not a creature and has the characteristics of a creature. Thus, this paper explains the method of translation and interpretation that is accurate and correct in line with the beliefs of ASWAJA in line with the opinions of the usuluddin scholars. Content analysis methods on some tafsir and usuluddin books have been used to obtain data and analyzed descriptively. The results of the study found that the method of interpretation and translation of the verses of Mutasyabihat in the Qur’an should follow the correct and accurate manhaj to maintain the purity of its meaning and avoid the interpretation of the mujassimah, mushabihah, and hashawiyyah who have strayed far.